Assessment of Knowledge, Attitude and Practice of Biosafety among University's Laboratory Staff - Nik Mohd Razali, Nik Nurfatin Athirah; Abdul Samad, Nurul Izzah; Mohd Amin, Nursuhaili; Yhaya, Mohd Firdaus; Hatta, Herdianti; Hamzah, Nurul Ainun (Knowledge Dynamics, 2025)
Background: Biosafety is crucial for protecting laboratory staff from infectious agents and hazardous biological materials. Inadequate knowledge of unsafe practices may increase the risk of laboratory-acquired infections and accidents. This study assessed the knowledge, attitude, and practice (KAP) of biosafety and related factors among laboratory staff. Methods: A cross-sectional study was conducted among 150 laboratory staff recruited through stratified and random sampling. Data were collected using a validated, self-administered questionnaire that assessed knowledge, attitude, and practice related to biosafety. Descriptive analysis, one-way ANOVA, Pearson correlation and multiple linear regression were performed to examine differences and associations. Results: The findings revealed that laboratory staff demonstrated moderate knowledge (74.8%), good attitudes (95.5%), and good practices (93.7%) towards biosafety. Significant differences in knowledge [F (2,147) = 23.7, p < 0.001] and practice [F(2,147) = 21.36, p < 0.001] were observed across schools. A moderate positive correlation was found between practice and knowledge (r = 0.518, p < 0.01) and between practice and attitude (r = 0.342, p < 0.01). Higher education was associated with better knowledge and attitudes, while longer years of employment were negatively associated with knowledge. No demographic factors significantly predicted practice. Conclusions: Laboratory staff demonstrated positive attitudes and good practices but showed only moderate knowledge of biosafety. Regular training, continuous education, and standardised biosafety programs are crucial for enhancing knowledge and maintaining safe laboratory practices. This study provides essential evidence to strengthen biosafety training and policies in Malaysian universities, supporting safer laboratory environments and improved institutional preparedness.